Cidadania organizacional e a liderança gerencial em empresas familiares nordestinas - Vieira Júnior, Holdemar Gonçalves (2015)
This paper aims to investigate the influence of management leadership style on the Organizational Citizenship Behavior in northeastern family business. Nine family companies operating in northeast Brazil were surveyed, that perform their activities in the segment of services. The targeting of research for the environment of family businesses is justified because they are the fastest growing organizations with great relevance and representation in the national market. These companies account for over 90% of the companies in Brazil, accounting for 60% of direct jobs and 48% of national production (GUEIROS, 1998). Representativeness and tradition in their workspace usas the selection criteria used in the companies suveyed. The data collection was carried out between January and April 2015, which were consulted 381 employees of these companies, using two research instruments already validated scientifically. To measure the behaviors relating to leadership styles was used the Management Style Assessment Scale (EAEG), as to assess the Organizational Citizenship Behaviors it was used the Organizational Citizenship Behaviors Scale (ECCO). It had been used descriptive statistics and factor analyzes to meet the goal of research that confirmed that the leadership style focused on the task is prevalent in family businesses. Otherwise, the Organizational Citizenship Behavior highest incidence is the cooperation with colleagues. In order to meet the purpose of which leadership style most influences the CCO, it was used the statistical techniques of structural equations to evaluate the correlation of these two constructs. Thus, it is concluded that the most correlation was the management style focused on the task and the CCO of the image promotion of organizations.